Analisis Harmonisa Tegangan dan Arus Listrik di Gedung Teknik Penerbangan Politeknik Penerbangan Indonesia Curug - Putri Anggraeni M; Suse Lamtiar Simbolon; IGK. Rai Darmaja (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
Electrical equipment can affect power quality. Especially non-linear loads such as (computers, electronic equipment, energy saving lamps, etc.). Measurements are needed to determine the power quality (harmonics) in the PPIC Aviation Engineering building. Measurements were made on Monday 3 August 2020 - Wednesday 5 August 2020. The highest harmonic measurement data was on Monday, 3 August 2020 with the THD value of the R phase current of 67.98%, S of 29.73%, and T of 87. 13%. The harmonic value of the measurement results exceeds the standard set by IEEE 519-1992. From the simulation results of tuned passive filter installation using ETAP 12.6.0 the harmonic value can be reduced. Before installing the Passive Single Tuned filter, the harmonic value on bus 5 was 58.11%. After installing the filter the harmonic value on bus 5 can be reduced to 12.58%.